Integration of Islamic Values in Electronic Comic Media on Vibration, Waves, and Sound - Ucca Swasti Praptiwi; Agus Yulianto; Ellianawati Ellianawati (International Conference on Science, Education, and Technology, 2021)
This comic electronic media is a comic that is uploaded on a webtoon. Students more easily access it via smartphones. This study aims to determine the feasibility of electronic comic media based on problem based learning integrated with Islamic values based on the assessments of material experts, media experts, and learning experts. This study uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique used is a research instrument with quantitative data analysis. The feasibility of material experts on each indicator obtained an average of 84.28% with very feasible criteria. Assessment from media experts received an average of 82.77% on each indicator with very decent standards. The feasibility of the media based on the evaluation of learning experts on each indicator obtained an average of 100.00% with very feasible standards. The test of electronic media based on Islamic-based learning problems shows the criteria are very feasible to be tested. This media can then be used as a science learning medium for vibration, waves, and sound materials in everyday life for grade VIII junior high school.